Pemetaan Lokasi Fishing Ground dan Status Pemanfaatan Perikanan di Perairan Selat Madura - Firman Farid Muhsoni; Mahfud Efendy; Haryo Triajie (Lambung Mangkurat University Press, 2009)
This research aims at finding the map of waters quality to predictfishing ground, examining the determinant of modeling parameter of fish catchingregion, analyzing catch unit effort (CpUE) and status of fish utilization. Mappingwaters quality parameter is constructed with method of field sample datainterpolation. Besides, the mapping of surface temperature and chlorophyll isextracted from satellite image Landsat. ETM+. In addition, the mapping ofcatching region is resulted in scoring and weighting factors. Accuracy test isdone by method of RMSE. Fishery utilization status is acquired from method ofapproaches holistic (production surplus model). Map waters salinity at straitsMadura ranges between 27 ppm - 46 ppm, pH range from 8-9, brightnessranges from 0-2 m. Sea level temperature from image landsat in dry seasonranges from 24,1 0C - 27,3 0C in rainy season between 24,7 0C - 28,6 0C.Optimum temperature in rainy season is lower than in dry season. Chlorophyll indry season ranges between 0 mg/m3 - 19,6 mg/m3, in rainy season between -0,02 mg/m3 - 41,95 mg/m3. In dry season, the most appropriate catching regionis 58,04 %, appropriate region 36,99% and inappropriate region 4,96 %, while inrainy season, inappropriate region achieves 94,44 %, appropriate 2,89 % andinappropriate 2,65 %. Sea level temperature accuracy test gets RMSE 2,32 andfor chlorophyll content 2,31. Fishery estimation result pelages get CpUE 0.10ton/trip with utilization status indicating over-fishing in tahun1997 and fisherydemersal CpUE 0.03 ton/trip with utilization status indicating a surplus incatching in last three year.